Non-Metric Dental Traits in Human Skeletal Remains from Transcaucasian Populations: Phylogenetic and Diachronic Evidence - Khudaverdyan, Anahit Yu. (Anthropological Review, 2014)
The aim of the study is the assessment of biological distance between populations from Transcaucasia on the basis of the frequency of dental morphological traits. It is well known that these traits are characterised by a high inter-population differentiation, low sexual dimorphism, and their recording is loaded by relatively small intra and inter observer error. The dental morphological traits are successfully used in the description and explanation of the microevolutionary and ethnogenetic processes. This paper presents the results of the odontological differentiation of human populations from Transcaucasia. The comparative analysis was carried out on the basis of 12 groups. From the obtained results, we can draw the following conclusions: The populations of Armenian Highland and Georgia can be differentiated as far as the frequency of dental morphological traits are concerned. They also do not exhibit similar intragroup variability. Biocultural diversity of ancient Transcaucasian populations has not been studied extensively; therefore, delineating some of the patterns of phenotypic variation may be useful for understanding their ongoing evolution.